Indonesian Values of Islamic Education in the Munggahan Tradition in Trimulyo Village - Firdausi, Fiyya Zahrotul; Yusuf, Muhammad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Tradition encompasses all inherited cultural practices from the past that continue to hold significance within a specific region. One such tradition is the